Some of us are looking [large type] - O'Connor, Carlene (O'Connor, Carlene. County Kerry mystery., 2023)
In Dimpna Wilde's veterinary practice, an imminent meteor shower has elevated the usual gossip to include talk of shooting stars and the watch parties that are planned all over Dingle. But there are also matters nearer at hand to discuss including the ragtag caravan of young people selling wares by the roadside, and the shocking death of Chris Henderson, an elderly local, in a hit-and-run. Just hours before his death, Henderson had stormed into the Garda Station, complaining loudly about the caravan's occupants causing noise and disruption. One of their members is a beautiful young woman named Brigid Sweeney, and Dimpna is shocked when Brigid later turns up at her practice, her clothing splattered in blood and an injured hare tucked into her shirt. Brigid claims that a mysterious stranger has been trying to obtain a lucky rabbit's foot. Dimpna is incensed at the thought of anyone mutilating animals, but there is far worse in store. On the night of the meteor shower, Dimpna finds Brigid s body tied to a tree, her left hand severed. She has bled to death. Wrapped around her wrist is a rabbit's foot. Brigid had amassed plenty of admirers, and there were tangled relationships within the group. But perhaps there is something more complex than jealousy at play. The rabbit's foot, the severed hand, the coinciding meteor shower the deeper Dimpna and Detective Sargeant Cormac O'Brien investigate, the more ominous the signs seem to be, laced with a warning that Dimpna fears it will prove fatal to overlook.